Penggunaan Google Classroom Sebagai Media Pembelajaran Matematika - Ellen Proborini; Ratna Herawati (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
The purpose of this study is determining the online mathematics learning implementation using Google classroom media for XII grades at SMK Tunas Harapan Pati, obstacles for using google classroom and amenity for using google classroom . This research uses qualitative research methods with descriptive design.The subject in this research is 5 students grade XII who are chosen with simple random sampling methods. The techniques used in collecting data are deep interview, and direct observation at the same time. Data analysis techniques use interactive data analys model. The conclusion of this research is the students can’t be optimally adapted in using google classroom for media of learning mathematics such as unstabile signal and there is electricity blackout too often .